2021
DOI: 10.1007/s11356-021-15835-w
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus removal in denitrifying woodchip bioreactors varies by wood type and water chemistry

Abstract: Denitrifying woodchip bioreactors are a practical nitrogen (N) mitigation technology but evaluating the potential for bioreactor phosphorus (P) removal is highly relevant given that (1) agricultural runoff often contains N and P, (2) very low P concentrations cause eutrophication, and (3) there are few options for removing dissolved P once it is in runoff. A series of batch tests evaluated P removal by woodchips that naturally contained a range of metals known to sorb P and then three design and environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Some ditches may run at least 400 m, and rather than running the entire parallel length, placing bioditch reactors in alternate sections of the ditch may be more beneficial for nutrient retention. Further potential lines of investigation include gas flux measurements to determine whether NO 3 − is completely denitrified to N 2 in these bioditch reactor environments, as well as other types of wood (Bustamante‐Bailon et al., 2022) or agricultural crop waste (e.g., corn cobs, rice straw, rice hulls, or Miscanthus straw) that may be utilized as reactor fill to address concerns of P loss from certain woodchip species.…”
Section: Discussionmentioning
confidence: 99%
“…Some ditches may run at least 400 m, and rather than running the entire parallel length, placing bioditch reactors in alternate sections of the ditch may be more beneficial for nutrient retention. Further potential lines of investigation include gas flux measurements to determine whether NO 3 − is completely denitrified to N 2 in these bioditch reactor environments, as well as other types of wood (Bustamante‐Bailon et al., 2022) or agricultural crop waste (e.g., corn cobs, rice straw, rice hulls, or Miscanthus straw) that may be utilized as reactor fill to address concerns of P loss from certain woodchip species.…”
Section: Discussionmentioning
confidence: 99%
“…Woodchips for both bioreactors were a ~70/30 mixture of hardwood/softwood that were double ground on a commercial-scale grinder, resulting in effective (D 10 ) and median (D 50 ) diameters of 2.9 and 5.0 mm, respectively. Initial woodchip drainable porosity and bulk density were 64% and 227 kg•m −3 , respectively [13,14]. The total contractor cost for the small amount of ditch shaping and materials for the in-ditch bioreactor plus the cost of excavating, filling, and materials for the diversion bioreactor was $8800.…”
Section: Bioreactor Design and Constructionmentioning
confidence: 99%
“…Pfannerstill et al indicated a reactive ditch bioreactor in Germany did not consistently reduce dissolved or total phosphorus concentrations or loads [6]. Although woodchips have been shown to reduce dissolved phosphorus concentrations [14,40,41], it is likely that sediment accumulation associated with an in-dich bioreactor would be a greater sink for phosphorus in-ditch drainage water. Burial of the woodchip bag due to settled sediment, however, impeded hydraulic connectivity between the water column and woodchips, limiting the ability of the bioreactor to achieve its primary objective of reducing nitrate loads.…”
Section: Bioreactor and Samplementioning
confidence: 99%